Urgensi Rehabilitasi Sosial Terhadap Narapidana Pecandu Narkotika Di Lingkungan Lembaga Pemasyarakatan - Raden Mas Dimas Pangestu; R. Rahaditya (UNES Law Review, 2023)
This article explores the urgency of social rehabilitation for drug-addicted inmates within the confines of correctional facilities. Substance abuse has become a serious issue affecting various segments of society, including those ensnared within the criminal justice system. Social rehabilitation within correctional institutions is crucial in addressing this problem. Through a rehabilitative approach, drug-addicted inmates can receive guidance, support, and the necessary skills to reintegrate into society as productive individuals. This article underscores the importance of social rehabilitation as an integral part of efforts to rehabilitate drug-addicted inmates, with the hope that these measures will have a significant positive impact on behavioral change and their overall recovery.